Self-Reported Halitosis in relation to Oral Hygiene Practices, Oral Health Status, General Health Problems, and Multifactorial Characteristics among Workers in Ilala and Temeke Municipals, Tanzania - C. M. Kayombo; E. G. Mumghamba (Hindawi Limited, 2017)
Aim. To assess self-reported halitosis, oral hygiene practices, oral health conditions, general health problems, sociodemographic factors, and behavioural and psychological characteristics among workers in Ilala and Temeke municipals. Materials and Methods. This was a cross-sectional descriptive study. Four hundred workers were recruited using a self-administered structured questionnaire. Results. Self-reported tooth brushing practice was 100%, tongue cleaning 58.5%, dental flossing 4.3%, gum bleeding on tooth brushing 79.3%, presence of hard deposits on teeth 32%, mobile teeth 15.3%, and self-reported halitosis (SRH) 48.5%. Tea users were 95%, coffee users 75.8%, smokers 21%, and alcohol consumers 47%. The SRH was significantly associated with bleeding gums, hard deposits, and mobile and malaligned teeth. Tongue cleaning and regular change of toothbrush were associated with low prevalence of SRH (P<0.001). Higher occurrence of SRH was significantly related to low education and smoking. Conclusion. Self-reported halitosis was prevalent among workers and was significantly associated with bleeding gums, hard dental deposits, mobile teeth, and smoking. All participants brushed their teeth and cleaned the tongue regularly but use of dental floss was extremely low. Oral health education and health promotion are recommended.